2018
DOI: 10.3847/1538-3881/aaab56
|View full text |Cite
|
Sign up to set email alerts
|

Magellan/PFS Radial Velocities of GJ 9827, a Late K dwarf at 30 pc with Three Transiting Super-Earths

Abstract: The Kepler mission showed us that planets with sizes between that of Earth and Neptune appear to be the most common type in our Galaxy. These "super-Earths" continue to be of great interest for exoplanet formation, evolution, and composition studies. However, the number of super-Earths with well-constrained mass and radius measurements remains small (40 planets with σ mass < 25%), due in part to the faintness of their host stars causing ground-based mass measurements to be challenging. Recently, three transiti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 67 publications
4
24
0
Order By: Relevance
“…This mass and radius would suggest that GJ 9827 b has an iron core that makes up a significant fraction of its mass, and could indicate that it has undergone a mantle-stripping collision with another body of a similar mass (Marcus et al 2010). A more recent analysis (Prieto-Arranz et al 2018), however, suggests that the mass of GJ 9827 b is not as high as suggested by Teske et al (2018) and, in fact, may have a composition similar to that of the Earth. This analysis also suggests that GJ 9827 c is also rocky, but that GJ 9827 d may retain a substantial, extended atmosphere.…”
Section: Introductionmentioning
confidence: 89%
See 3 more Smart Citations
“…This mass and radius would suggest that GJ 9827 b has an iron core that makes up a significant fraction of its mass, and could indicate that it has undergone a mantle-stripping collision with another body of a similar mass (Marcus et al 2010). A more recent analysis (Prieto-Arranz et al 2018), however, suggests that the mass of GJ 9827 b is not as high as suggested by Teske et al (2018) and, in fact, may have a composition similar to that of the Earth. This analysis also suggests that GJ 9827 c is also rocky, but that GJ 9827 d may retain a substantial, extended atmosphere.…”
Section: Introductionmentioning
confidence: 89%
“…In addition to the HARPS-N and HARPS spectra, we also include in our analysis the Magellan/PFS observations first presented by Teske et al (2018). Thirty-six PFS observations were taken between January 2010 and August 2016, using the Planet Finder Spectrograph (PFS: Crane et al 2006) on the Magellan II (Clay) Telescope.…”
Section: Previously Published Magellan/pfs and Not/fies Spectroscopymentioning
confidence: 99%
See 2 more Smart Citations
“…K2-133 is comparable to the GJ-9827 system -three super-Earths orbiting a late K star with radii 1.6, 1.2 and 2.0 R ⊕ (Niraula et al 2017), which has been studied in great detail with precise radial velocity measurements (Teske et al 2018;Prieto-Arranz et al 2018;Rice et al 2019). A similar follow-up study of K2-133 would be interesting as a comparison to the GJ 9827 system.…”
Section: Radius Gapmentioning
confidence: 97%